Determination of heavy metals in medicinal plants from the wild and cultivated garden in Wilberforce Island, Niger Delta region, Nigeria - Edebi N. Vaikosen; Gideon O. Alade (GarVal Editorial Ltda., 2017)
Context: Adverse effects from herbal medicines may be partly due to the association of heavy metals with medicinal plants. Aims: To determine residual levels of Ni, Cr, Pb and Cd in nine selected medicinal plant species and the surrounding soils collected from the Faculty of Pharmacy medicinal garden and College of Health Sciences residential quarters, Amassoma, Bayelsa state, Nigeria. Methods: Nine plant species: Jatropha tanjorensis, Ipomoea batatas, Celosia argentea, Zea mays, Colocasia esculenta, Corchorus olitorius, Vernonia amygdalina, Ocimum gratissimum and Talinum triangulare were collected with their surrounding soil samples. The samples were dried and subjected to atomic absorption spectrophotometry (AAS) to determine the heavy metal concentrations. Results: The detection frequencies of heavy metals in medicinal plants were: Cd - 100%, Pb - 11%, Ni - 0% and Cr - 0%. The residential quarter was more contaminated than cultivated medicinal garden. Order of residual concentration in bulk soils was Cr > Cd > Ni > Pb. Bioaccumulation factor ranged from 0 - 25.93 for foliar tissues. Cadmium in plant species ranged from 0.23 to 2.44 µg/g with > 88% exceeding the WHO maximum limit for medicinal plant materials. Conclusions: The heavy metal concentrations in medicinal plants were dependent on the collection sites, plant species and physico-chemical properties of soil. Cd exhibited the greatest bioavailability in the investigated plants and soils. Cd and Pb found in plant foliage were due to uptake from soil and aerial deposition, respectively.